Mobile app for used item giveaway - Yeo, Bjorn Wen Zong (Nanyang Technological University, 2021)
The objective of the project is to design and develop a Mobile Application that provides an avenue for users to donate to or receive used items from others. The project is constructed using Swift as the main programming language to develop an iOS application.